2012
DOI: 10.1007/s10535-012-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N<sup>6</sup>-benzyladenine and indole-3-butyric acid on photosynthetic apparatus of Orthosiphon stamineus plants grown in vitro

Abstract: The leaf structure and chloroplast ultrastructure of kidney tea (Orthosiphon stamineus Benth.) was studied in in vitro culture on standard MS medium supplemented with or without plant growth regulators (PGRs). The cytokinin N 6 -benzyladenine (BA) negatively affected the structure of the palisade parenchyma and chloroplast ultrastructure and increased the stomatal frequency of the adaxial epidermis. The auxin indole-3-butyric acid (IBA) did not modify the morphology of regenerated leaf tissues as well as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Accordingly, the relationship between starch accumulation in tissues and regeneration potential has been reported for many species (Chen and Ziv, 2005;Fortes and Pais, 2000). Studies have indicated that higher starch levels are correlated with higher regeneration potentials (Chen and Ziv, 2005;Stoyanova-Koleva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the relationship between starch accumulation in tissues and regeneration potential has been reported for many species (Chen and Ziv, 2005;Fortes and Pais, 2000). Studies have indicated that higher starch levels are correlated with higher regeneration potentials (Chen and Ziv, 2005;Stoyanova-Koleva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, a common reaction to low temperatures is a collapse of the photosynthetic apparatus (Danova et al 2009, Ganeva et al 2009. Studies of the leaf structure of in vitro cultured plants revealed that the examination on subcellular level is very important for evaluation of plant regeneration potential (Stefanova 2011, Stoyanova-Koleva et al 2012.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%